W. Va. Code, ch. 153, §8 (1868) - (:unkn) unknown (My University, 1868)
Required any person going armed with any dirk, dagger, sword, pistol, or other offensive and dangerous weapon to post a surety once a complaint was filed, having cause to fear an injury or breach of the peace. Appeals provided for the accused.
Keywords: CARRY - INTENT TO COMMIT CRIME